SUMBER ETIKA DALAM ISLAM - Hardiono, Hardiono (JURNAL AL-AQIDAH, 2020)
In this paper, we will discuss the ethical problems generated by Islam as was directly exemplified by the pioneer, enlightener and role model of all followers, namely the Prophet Muhammad SAW. The source of ethics in Islam (Islamic ethics) is the al-Qur'an and the Sunnah, both of which are always a measure of the merits of the actions committed by the Muslims. These two sources are a guide for human life to achieve happiness in this world and in the hereafter.    The Prophet's behavior is the most factual interpretation of the Koran. In fact, in many narrations it is emphasized that the Prophet did not act / behave but because of the guidance of revelation, and the Prophet's morals were al-Qur'an. That is why in Islamic scholarship, including Islamic ethics, it does not give up its premises from the Qur'an and the Sunnah of the Prophet SAW. In Islam, the Quran and Sunnah will teach adherents from all sides, be it social, religious, cultural and so on. So in this paper we will discuss the sources of ethics in Islam (Islamic Ethics).            The method of this research is library research (library research), namely research that uses literature in the form of books, notes and reports on the results of previous research which will later become an analysis tool regarding ethics in Islam.     The conclusion of this paper is that the source of ethics in Islam is al-Quran and as-Assunah, which  will be the life guide for Muslims and non-Muslims to achieve true happiness, which the Prophet had exemplified directly from the above source.